History, Holocaust, and Revelation: Beyond the Barthian Limits - Lindsay, Mark R. 1971- (2005)
This article explores the still-unresolved question surrounding the relationship of history to theology, specifically the role of traumatic history in the formulation of theological discourse. It is suggested here that, in order for theology to address adequately the needs of contemporary culture, a revision of the traditional concept of revelation is required, so that historical events can be seen as revelatory in themselves, while simultaneously maintaining the integrity of the revelation-idea and the historical particularities of the events themselves. The Holocaust serves as a paradigm of history-as-revelation, while the work of Dietrich Ritschl provides a model for the redefinition of revelation.